Neutralization of Wastewater Obtained from the Production of Alkyd Resins - Aykan, N.F.; Malikova, I.H.; Efendi, A.C.; Babayev, E.M.; Rustamova, C.T.; Aliyeva, N.R.; Yunusova, F.A. (Herald of Azerbaijan Engineering Academy, 2022)
The main pollution index of wastewater contaminated with organic compounds – COD of wastewater obtained from the production of alkyd resins – varies between 20000-40000 mg/L. 50% reduction in the amount of organic compounds has been achieved in wastewater treatment using aeration, acid cracking, oxidation process and their combined methods. Chemical oxidation has been carried out with hydrogen peroxide and Fenton's reagent. Oxidation with hydrogen peroxide in an acidic medium led to the removal of 50% of organic compounds. This value in the Fenton reaction – advanced oxidation was up to 60%, the optimal mode of this process has been established.